COMPRESSED FLANGES OF ARCHED STEEL THIN-WALLED COLD-ROLLED PROFILED SHEETS: DETERMINATION OF RESIDUAL STRESSES - S. A. Makeev; V. A. Gorkovenko; E. A. Seitov; L. F. Rahuba (Вестник СибАДИ)
Introduction. The construction sphere widely uses steel thin-walled cold-formed profiles. In arched steel coldformed trapezoidal section profiles, residual normal stresses oriented along the profile occur at the stage of manufacturing arched blanks from flat profiled sheets and are caused by the cold bending process involving the extreme zones of the profile in the plastic stage with unloading without subsequent heat treatment. According to preliminary estimates, the residual stresses are up to one third of the calculated resistance of sheet steel at small radii of the arch profile. At present, the researchers do not take into account the residual technological stresses of the longitudinal bending when designing structures from thin-walled longitudinally bent rolled trapezoidal sections. The purpose of the paper is to develop a method for determining residual stresses in compressed flanges of arched steel thin-walled cold-rolled profiled sheets, which provides simplicity of the measurement and calculation methods, reliability and high accuracy of the obtained stress values.Materials and methods. The authors made the analysis of previously published materials and identified the advantages and disadvantages of previous studies. Moreover, the authors showed the advantages of the proposed method for determining the residual technological normal stresses in compressed flanges of arched steel thin-rolled profiled steel.Results. The researches formed a new method for making sections of a compressed shelf and measuring residual normal stresses in the compressed flanges of an arched steel sheet of cold-rolled profiled steel. The proposed method greatly simplified the existing method of determining residual technological normal stresses in compressed profile flanges, improved the accuracy of measuring normal stresses in compressed profile flanges.Discussion and conclusions. The method of measuring residual process stresses allows improving existing methods for determining residual stresses, simplifying calculations, as well as improving the accuracy of stresses. In the future, the authors will make a numerical simulation of the bending arch profiles, as well as an experimental assessment of the adequacy of the proposed method.The authors have read and approved the final manuscript. Financial transparency: the authors have no financial interest in the presented materials or methods. There is no conflict of interest.